2010
DOI: 10.1038/aja.2010.23
|View full text |Cite
|
Sign up to set email alerts
|

Treatment satisfaction after 1 year high-power potassium-titanyl-phosphate photoselective vaporization of the prostate

Abstract: To investigate the factors that influence treatment satisfaction after high-power potassium-titanyl-phosphate (KTP) laser vaporization of the prostate, we compared the characteristics between patients who were satisfied and those who were not satisfied. In all, 97 patients aged between 53-82 years (median age 67 years) underwent high-power KTP laser vaporization of the prostate for lower urinary tract symptoms due to benign prostatic hyperplasia. At 12 months postoperatively, 60 patients were satisfied with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Mishiriki et al reported that 8.4%, 20.8%, and 13.3% of patients were dissatisfied after TURP at 6 months, 6 years, and 12 years, respectively [ 23 ]. Malek et al reported that 90% of the patients were very satisfied with potassium titanyl-phosphate photoselective vaporisation of the prostate [ 24 ], whereas Ku et al reported that 37 of the 97 patients were dissatisfied at 12 months postoperatively, and the reason for dissatisfaction was weak detrusor contractility [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mishiriki et al reported that 8.4%, 20.8%, and 13.3% of patients were dissatisfied after TURP at 6 months, 6 years, and 12 years, respectively [ 23 ]. Malek et al reported that 90% of the patients were very satisfied with potassium titanyl-phosphate photoselective vaporisation of the prostate [ 24 ], whereas Ku et al reported that 37 of the 97 patients were dissatisfied at 12 months postoperatively, and the reason for dissatisfaction was weak detrusor contractility [ 25 ].…”
Section: Discussionmentioning
confidence: 99%